1982
DOI: 10.1029/jb087ib11p09340
|View full text |Cite
|
Sign up to set email alerts
|

Elastic moduli, thermal expansion, and inferred permeability of two granites to 350°C and 55 megapascals

Abstract: The coefficient of thermal linear expansion α, Young's modulus E, and bulk modulus K have been determined for the Westerly and Stripa granites to temperatures T of 350°C and pressures P to 55 MPa. Using conventional triaxial aparatus, displacement measurements were made on three samples from each of three orthogonal directions for both rocks. Comparison of the directional values at any P, T, and those from the nine‐sample population indicated that within our precision, both granites are isotropic in E, K, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 29 publications
5
87
0
Order By: Relevance
“…11 has also been observed in other studies (Heard and Page 1982;Klug and Cashman 1996;Saar and Manga 1999;Rust and Cashman 2004;Stimac et al 2004;Mueller et al 2008;Wright et al 2009;Heap et al 2014;Farquharson et al 2015;Wadsworth et al 2016;Heap and Kennedy 2016). There is scatter in the relationship, which results from the geometry and connectivity of the pores (as noted in Mueller et al 2008 and others), amongst other factors.…”
Section: Connected Porosity-permeability Relationshipmentioning
confidence: 58%
“…11 has also been observed in other studies (Heard and Page 1982;Klug and Cashman 1996;Saar and Manga 1999;Rust and Cashman 2004;Stimac et al 2004;Mueller et al 2008;Wright et al 2009;Heap et al 2014;Farquharson et al 2015;Wadsworth et al 2016;Heap and Kennedy 2016). There is scatter in the relationship, which results from the geometry and connectivity of the pores (as noted in Mueller et al 2008 and others), amongst other factors.…”
Section: Connected Porosity-permeability Relationshipmentioning
confidence: 58%
“…At zero confining pressure, the force of the piston probably deforms the sample a small amount, which can be ignored. This technique was first used by Heard and Page [1982] to measure thermal expansivity of rocks under pressure.…”
Section: Methodsmentioning
confidence: 99%
“…Typical values for the thermal expansion coefficient for saturated rock at high temperature and pressure range from 5 Â 10 À6°CÀ1 to 1.5 Â 10 À5°CÀ1 [Bauer and Handin, 1983;Heard and Page, 1982;Wong and Brace, 1979], and we use a value of 1 Â 10 À5°CÀ1 in all simulations. Crustal deformation scales inversely with shear (rigidity) modulus, and laboratory experiments at high pressures and temperatures indicate that the intrinsic shear modulus of crystalline rocks varies from 0.2 to 50 GPa depending on rock type, temperature, pressure, and porosity [Heard and Page, 1982]. Although large-scale crustal values of 30 GPa [Turcotte and Schubert, 2002] are commonly invoked in elastic deformation models, several studies have suggested that the rigidity of warm volcanic rocks should be as low as 0.3 GPa [e.g., Davis, 1986].…”
Section: à2mentioning
confidence: 99%